A Preclinical Model to Study the Influence of Graft Force on the Healing of the Anterior Cruciate Ligament Graft - Ma, Richard; Stasiak, Mark; Deng, Xiang-Hua; Rodeo, Scott A. (The Journal of Knee Surgery, 2019)
The purpose of this study is to establish a small animal anterior cruciate ligament (ACL) reconstruction research model where ACL graft force can be varied to create different graft force patterns with controlled knee motion. Cadaveric (n = 10) and in vivo (n = 10) rat knees underwent ACL resection followed by reconstruction using a soft tissue autograft. Five cadaveric and five in vivo knees received a nonisometric, high-force femoral graft tunnel position. Five cadaveric and five in vivo knees received a more isometric, low-force graft tunnel position. ACL graft force (N) was then recorded as the knee was ranged from extension to 90 degrees using a custom knee flexion device. Our results demonstrate that distinct ACL graft force patterns were generated for the high-force and low-force femoral graft tunnels. For high-force ACL grafts, ACL graft forces increased as the knee was flexed both in cadaveric and in vivo knees. At 90 degrees of knee flexion, high-force ACL grafts had significantly greater mean graft force when compared with baseline (cadaver: 7.76 ± 0.54 N at 90 degrees vs. 4.94 ± 0.14 N at 0 degree, p = 0.004; in vivo: 7.29 ± 0.42 N at 90 degrees vs. 4.74 ± 0.13 N at 0 degree, p = 0.007). In contrast, the graft forces for low-force ACL grafts did not change with knee flexion (cadaver: 4.94 ± 0.11 N at 90 degrees vs. 4.72 ± 0.14 N at 0 degree, p = 0.41; in vivo: 4.78 ± 0.26 N at 90 degrees vs. 4.77 ± 0.06 N at 0 degree, p = 1). Compared with nonisometric ACL grafts, the graft force for grafts placed in an isometric position had significantly lower ACL graft forces at 15, 30, 45, 60, 70, and 90 degrees in both cadaveric and in vivo knees. In conclusion, we have developed a novel ACL reconstruction model that can reproducibly produce two ACL graft force patterns. This model would permit further research on how ACL graft forces may affect subsequent graft healing, maturation, and function.
Keywords: anterior cruciate ligament; graft isometry; tunnel position; ACL healing